Reading in the dark : using film as a tool in the English classroom - Golden, John, 1968- (Urbana, Ill. : National Council of Teachers of English, 2001)
A practical guide to using films as texts in English classes, which discusses reading strategies and textual analysis; explains terminology and cinematic effects using over thirty films as examples; presents unit suggestions for eleven films; and provides a glossary, blank activity charts, and an annotated resource list.
Includes bibliographical references.
Professional.
Professional
Keywords: Language arts (Middle school); Motion pictures in education; Language arts; Motion pictures in education